Factors Affecting Superoxide Dismutase Activity in Railway Workers in Jakarta, Indonesia - Winata, Vera; Ilyas, Muhammad; Kekalih, Aria; Wibowo, Suryo; Mansyur, Muchtaruddin (Occupational and Environmental Medicine Journal of Indonesia, 2024)
Introduction. Railway workers are exposed to many occupational health risk factors that may cause oxidative stress. Superoxide dismutase (SOD) activity is one of the response biomarkers of oxidative stress. Methods. A cross-sectional study was conducted from July-October 2021. Eighty-four participants were included in this study. Data about participants’ characteristics, physical activity intensity as measured by the Global Physical Activity Questionnaire (GPAQ) version 2, and stress levels as measured by Holmes-Rahe Stress Inventory were collected using Google Forms. The physical examination yielded data on blood pressure, ear condition, and waist circumference. Blood Superoxide dismutase activity and HbA1c levels were determined using the spectrophotometry assay method. Univariate, bivariate, and multivariate analyses were done using the chi-square test and logistic regression. Results. The proportion of administrative workers with high SOD activities was 78.6% compared to train drivers (33.3%). Administrative workers were 7.1 times more likely to have high SOD activity than train drivers (aOR = 7.1, p-value Conclusion. The train company administrative workers exhibited higher Superoxide Dismutase activity than train drivers. Future study and occupational health programs are needed to investigate occupational factors affecting oxidative stress to prevent potential health disorders.